Students’ Response Toward Online Arabic Lenguage Learning in Madrasah Tsanawiyah Negeri Surakarta 1/ Respon Siswa Terhadap Pembelajaran Bahasa Arab daring di Madrasah Tsanawiyah Negeri Surakarta 1 - Rohas, Jauharul; Saputro, Duwi (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2021)
This study aims to determine student responses to learning Arabic online at Madrasah Tsanawiyah Negeri Surakarta 1. The research method uses descriptive methods with a questionnaire technique by asking as many as 5 questions to students of MTs Negeri Surakarta 1 class VII, VIII, and IX as many as 417 through filling in the questions distributed to all respondents in the form of google form. Based on the data, it was found that the Arabic learning media most used by teachers was WhatsApp, while the media most liked by students when learning Arabic online was What's App with 47% of respondents, Goole Meet 22% of respondents, and Google Classroom 22% of respondents. The problems faced by students during online learning are (1) Students have difficulty understanding the material 51% of respondents (2) No quota 8% of respondents (3) Internet networks are often disconnected 13% of respondents (4) Lack of direct explanation of the material using Google meet, zoom 23% of respondents (5) Number of tasks given by the teacher 5% of respondents. Learning Arabic online is still a lot of problems because a teacher and an institution are more prepared for online learning.